The BEAF-32 insulator coordinates genome organization and function during the evolution of Drosophila species - Yang, Jingping; Ramos, Edward; Corces, Victor G. (Genome Research, 2012)
Understanding the relationship between genome organization and expression is central to understanding genome function. Closely apposed genes in a head-to-head orientation share the same upstream region and are likely to be coregulated. Here we identify the Drosophila BEAF-32 insulator as a cis regulatory element separating close head-to-head genes with different transcription regulation modes. We then compare the binding landscapes of the BEAF-32 insulator protein in four different Drosophila genomes and highlight the evolutionarily conserved presence of this protein between close adjacent genes. We find that changes in binding of BEAF-32 to sites in the genome of different Drosophila species correlate with alterations in genome organization caused by DNA rearrangements or genome size expansion. The cross-talk between BEAF-32 genomic distribution and genome organization contributes to new gene-expression profiles, which in turn translate into specific and distinct phenotypes. The results suggest a mechanism for the establishment of differences in transcription patterns during evolution.
10.1101/gr.142125.112